Tooth implant connected fixed partial denture: 3-year follow-up - T Anjan Kumar; N Gopi Chander; J Brintha Jei (SRM Journal of Research in Dental Sciences, 2018)
The natural tooth implant connected fixed partial denture is subjected to debate. Literature was suggestive of both for and against the connection. The connection of implant to natural tooth has advantages and disadvantages. The intrusion of the teeth, biomechanical mismatch between tooth and implant, and marginal bone loss are associated limitations in implant tooth connection. The reduction in cost, anatomical limitations, and reduced surgical intervention were of suggestive of the connection. This clinical report was discussed on the 3-year follow-up of the tooth connected implant-supported fixed partial, and the procedures were followed in the fabrication of prosthesis that aided in the success of the restoration.